Comprehensive assessment of rheumatoid arthritis susceptibility loci in a large psoriatic arthritis cohort - Mc Manus, Ross; Kane, David (My University, 2012)
Objective: A number of rheumatoid arthritis (RA) susceptibility genes have been identified in recent years. Given the overlap in phenotypic expression of synovial joint inflammation between RA and psoriatic arthritis (PsA), the authors explored whether RA susceptibility genes are also associated with PsA. Methods: 56 single nucleotide polymorphisms (SNPs) mapping to 41 genes previously reported as RA susceptibility loci were selected for investigation. PsA was defined as an inflammatory arthritis associated with psoriasis and subjects were recruited from the UK and Ireland. Genotyping was performed using the Sequenom MassArray platform and frequencies compared with data derived from large UK control collections. Results: Significant evidence for association with susceptibility to PsA was found to a SNP mapping to the REL (rs13017599, p trend =5.2?10 4 ) gene, while nominal evidence for association (p trend <0.05) was found to seven other loci including PLCL2 (rs4535211, p=1.7?10 ?3 ); STAT4 (rs10181656, p=3.0?10 ?3 ) and the AFF3 , CD28 , CCL21 , IL2 and KIF5A loci. Interestingly, three SNPs demonstrated opposite effects to those reported for RA. Conclusions: The REL gene, a key modulator of the NF ? B pathway, is associated with PsA but the allele conferring risk to RA is protective in PsA suggesting that there are fundamental differences in the aetiological mechanisms underlying these two types of inflammatory arthritis
ACCEPTED
Keywords: Rheumatoid arthritis (RA); Single nucleotide polymorphisms; Psoriatic arthritis; rheumatoid arthritis (RA); Genes & Society; Immunology, Inflammation & Infection